Are farmers using cropping system intensification technologies experiencing poverty reduction in the Great Lakes Region of Africa? - Dontsop Nguezet, Paul M.; Ainembabazi, John H.; Alene, A.; Abdulaye, T.; Feleke, S.; Nziguheba, G.; Khonje, M.; Mignouna, Djana B.; Okafor, C.; Njukwe, E.; Asten, Piet J.A. van; Mapatano, S.; et al. (Wiley, 2020)
This study evaluated the poverty reduction impact of the adoption of cropping system intensification (CSI) technologies using the endogenous switching regression (ESR) model in the Great Lakes region of Africa that comprises Burundi, eastern DR Congo, and Rwanda. The study data came from a household survey of 1,495 sample households interviewed between October and December 2014. Results indicated that the adoption of the CSI technologies had increased crop yield, crop income, and per capita consumption expenditure in the region, resulting in poverty reduction. Among the three countries, eastern DR Congo witnessed the highest poverty reduction (13% points) followed by Rwanda (6% points) and Burundi (2% points). Considering the adoption rate and size of the target population in each country at baseline, an estimated 180 thousand poor individuals had escaped poverty due to the adoption of the CSI technologies. This presents important evidence in favor of promoting CSI technologies as part of poverty reduction strategy. Given the large population size that remains poor even after adoption, we suggest that research‐based poverty reduction strategies such as the CSI technologies should be complemented with development interventions.